The Role of export in the economic development of Korea - Dessalegn, Yigzaw (KDI School, 1998)
Exporters in Korea did get an adequate export subsidy to reduce the trade bias from the existing protection provided to the majority of import competing industries. This is not true, however, in the case of few import competing industries, which received higher effective rate of protection in the domestic market. In turn, for those industries with relatively higher protection in the domestic market sales in the profitable domestic market was used as an incentive for an adequate export performance. The incentive structure also shows a higher variation among import-competing industries than exporting industries. The higher magnitude of variation in incentives among import competing industries also shows the presence of an industry bias. The industry bias among import competing industries, on the other hand, shows the dominant role of government intervention in the allocation of incentives among each industry group. In contrast, the lower variation of incentives among exporting industries shows the dominant role of the market mechanism, through export performance measure, in the allocation of incentives than government intervention. Neutral incentive trade regime on average was established because higher incentives to few import-competing industries were offset by lower incentives to other import-competing industries. The presence of an aggregate neutral incentive trade regime in Korea in the early period of the export promotion strategy also shows that the promotion of few import-competing industries at a time through biased incentives did no tcreate a significant resource bias against exporters. The incentive structure, which increases the relative profitability to exports were also the main factor behind rapid export growth in Korea. Higher rate of export growth through its beneficial impact on resource allocation, investment growth and productivity led to rapid economic growth in Korea. Economic development in Korea was made far more sustainable due to the presence of educated manpower to adopt improved foreign technology made accessible from competition in the international market.
Thesis(Master) --KDI School:Master of International Economic Policy,1998